Matematyka
dzaruga
1

a ) (3^7 * 3^-9) : 3^-6 = b ) (2^3-2^2*2^0) * 0,25 ^4 c ) 4^-10 * ( 8^3-2^9) d ) (18^2-12^3) * 36^3

+0
(1) Odpowiedź
Kaasiek08

A ) [latex](3^7 \cdot 3^{-9}) : 3^{-6} =3^{7-9} : 3^{-6} =3^{-2} : 3^{-6} =[/latex] [latex]3^{-2-(-6)} =3^{-2+6} =3^4=81[/latex] b ) [latex](2^3-2^2 \cdot 2^0) \cdot 0,25 ^4=(2^3-2^{2+0}) \cdot \left( \frac{1}{4} \right) ^4=[/latex] [latex](2^3-2^2) \cdot \left( \frac{1}{2^2} \right) ^4=(8-4) \cdot 2^{-8}=[/latex] [latex]4 \cdot 2^{-8}=2^2 \cdot 2^{-8}=2^{2-8}=2^{-6}= \frac{1}{64}[/latex] c ) [latex]4^{-10} \cdot ( 8^3-2^9)=(2^2)^{-10} \cdot ( (2^3)^3-2^9)=[/latex] [latex]2^{-20} \cdot ( 2^9-2^9)=2^{-20} \cdot 0=0[/latex] d ) [latex](18^2-12^3) \cdot 36^3 =(324-1728) \cdot 46656=-1404\cdot 46656=-65505024[/latex]

Dodaj swoją odpowiedź